Fuselage Crashworthiness Lower Lobe Dynamic Test. (2016) - Marulo, F.; Guida, M.; Di Caprio, F.; Ignarra, M.; Lamboglia, A.; Gambino, B.
Abstract: The focus of this paper is to demonstrate the energy absorption capability of the lower lobe section of the aircraft, and to provide test data in support of validation of the LS-DYNA numerical model. Following a national research program, a full scale drop test, of an airliner composite sub cargo floor fuselage, has been performed by the Italian Aerospace Research Center (CIRA) at their LISA (Laboratory for Impact testing of Structures in Aerospace field) facility. The ultimate aims of research are design, size and evaluation of the crash behaviour of a specific concept of composite aircraft fuselage section linked to the full scale tests. The results are based on pre-test simulations performed on coupon including representative elements devoted to the absorbption of the crash energy, and finally with the final drop test results and the corresponding post-test simulations. Test provides validation of LS-DYNA analysis, and using the simulation tools it is possible to quantify different parameters as energy distribution, accelerations, dynamic structural efficiency, and structural deformations throughout the crash event, but above all the importance to define the real conditions of the constraints and loads in the attempt to reproduce the behaviour of the full scale aircraft fuselage, or section of it, during an emergency landing condition, partially reduced to the full scale subfloor. Then the simulation allows to develop geometries and size of the structures with stanchions and other structural elements in order to reduce the energy absorbing capabilities of the cargo subfloor. Test data indicates the cargo subfloor can absorb an impact velocity of 22 feet/sec with typical payload, and the certification requirements about the emergency landing as satisfied. Finally, the decelerations and deformations are restricted in a survivable space for the passenger compartment.